Learning to Export : Evidence from Moroccan Manufacturing - Fafchamps, Marcel; El Hamine, Said; Zeufack, Albert (World Bank, Washington D.C., 2013)
The authors test two alternative models of learning to export: productivity learning, whereby firms learn to reduce production cost, and, market learning, whereby firms learn to design products that appeal to foreign consumers. Using panel, and cross-section data on Moroccan manufacturers, the authors uncover evidence of market learning, but little evidence of productivity learning. These findings are consistent with the concentration of Moroccan manufacturing exports in consumer items - the garment, textile, and leather sectors. It is the young firms that export. Most do so immediately after creation. The authors also find that, among exporters, new products are exported very rapidly after production has begun. The share of exported output nevertheless, increases for 2-3 years after a new product is introduced. Old firms are unlikely to switch to exports, even in response to changes in macroeconomic incentives. The authors find a positive relationship between exports, and productivity, and conclude that it is the result of self-selection: it is the more productive firms that move into exports. Policy implications are discussed.